The Millicent Quibb school of etiquette for young ladies of mad science. 2, Secrets of the purple pearl - McKinnon, Kate, 1984- (McKinnon, Kate, 1984- Millicent Quibb School of Etiquette for Young Ladies of Mad Science (Series), 2025)
"Three orphaned siblings discover more about mad science and themselves under the tutelage of their beloved professor, Millicent Quibb"--